"Unplugged, " a European school‐based program for substance use prevention among adolescents: Overview of results from the EU‐Dap trial. Issue 141 (March 2014) - Vigna‐Taglianti, Federica D.; Galanti, Maria Rosaria; Burkhart, Gregor; Caria, Maria Paola; Vadrucci, Serena; Faggiano, Fabrizio
Abstract : The EU‐Dap study aimed to develop and evaluate a school‐based curriculum for the prevention of substance use among young people. The school curriculum, "Unplugged, " is based on social influence approach and addresses social and personal skills, knowledge, and normative beliefs. It consists of 12 one‐hour interactive sessions delivered by teachers. Its effectiveness was evaluated through a randomized trial involving 7, 079 pupils of seven European countries. Unplugged was effective in reducing cigarette smoking, episodes of drunkenness, and the use of cannabis at short term. This association, however, was confined to boys, with age and self‐esteem as possible explanations of this difference. Beneficial effects associated with the program persisted at fifteen‐month follow‐up for drunkenness, alcohol‐related problems, and cannabis use, and were stronger among adolescents in schools of average low socioeconomic level. These results are of scientific importance and may inform the adoption of effective public health interventions at population level.